Experiences of dog theft and spatial practices of search/ing. Issue 4 (11th August 2022) - Allen, Daniel; Arathoon, Jamie; Selby‐Fell, Helen
Abstract: Public responses to an 'upward trend' in recorded dog theft offences in England and Wales led to the creation of the Pet Theft Taskforce in May 2021, followed by a policy paper recommending the development of a new 'pet abduction' offence. Despite this, the experiential nature of dog theft, what impact this has on victims, and how they go about searching for their stolen dogs have been overlooked. Building on interdisciplinary research on dog theft, and wider literature on the impact of absence and loss on human victims, this paper explores the experiential dimension of this crime and the spatial and temporal practices of search/ing. Drawing on 15 semi‐structured interviews with victims of dog theft (10) and community resolution groups (5), key themes emerged from our analyses: (i) more‐than‐human families and (ii) spatial and temporal practices of search/ing. The dogs in this study occupy an absent presence, their bodies not visibly present but occupying a space in the minds and words of their humans. From the realisation of loss through to ongoing searches to possible reunite, participant experiences are filled with emotions that reflect a traumatic experience and 'ambiguous absence'. With expectations of police support rarely met, victims started physically searching themselves, moving from the local to regional and national, while connecting with animal professionals and community resolution groups. Virtual space was seen as vital, with social media amplifying the virtual presence of specific stolen dogs. Conceived as a more‐human‐focused animal geography, the research brings together an empirical example at the potential intersection of animal geographies and policing. The experiential evidence in this paper suggests changes to organisational practices (standardised police approach; centralised microchip database; mandatory microchip‐scanning by animal professionals) and national government policy interventions ('pet abduction' offence) might have a positive impact on victim experiences. Abstract : Building on interdisciplinary research on dog theft, and wider literature on the impact of absence and loss on human victims, this paper explores the experiential dimension of this crime and the spatial and temporal practices of search/ing. Drawing on 15 semi‐structured interviews with victims of dog theft (10) and community resolution groups (5), key themes emerged from our analyses: (i) more‐than‐human families and (ii) spatial and temporal practices of search/ing. The experiential evidence in this paper suggests changes to organisational practices (standardised police approach; centralised microchip database; mandatory microchip‐scanning by animal professionals) and national government policy interventions ('pet abduction' offence) might have a positive impact on victim experiences.